Using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model to Study Investors’ Buying Behaviour Towards Mutual Funds - Pushpa Raj K; Shyamaladevi Balakrishnan (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: In recent years, we have witnessed tremendous growth in mutual funds in India. There are many reasons behind this growth trajectory, including diversification, compounding, and a lesser involvement of investors in tracking the performances of individual stocks. Technology has allowed investors to choose their funds based on their risk appetite and tenure when they need their investments to mature. The current advancement in digital technology created a more accessible platform for investors to choose different investment vehicles quickly. Mutual funds are among the most well-liked investment choices, for small-scale investors, as they offer steady income over a more extended period with lesser risk. Digitalisation has led more investors to move towards mutual funds as it involves less paperwork to start investing. Also, digital payments have eased investors’ lives by allowing them to make payments safely and securely without needing to reach Asset Management Companies (AMCs). In this study, we have attempted to study the impact of different variables that affect mutual fund subscriptions. Design/Methodology/Approach: To demonstrate the causal connection between the various variables, the Structural Equation Modelling (SEM) technique has been employed. We employed a variance-based technique using PLS in our study. With the aid of SmartPLS 3.0, the study model was verified. We follow the normal two-step process, with the first step being the assessment of the measurement model and the second stage is to evaluate models for measurements and structures. Research findings: The two new additional variables introduced in this study were strongly significant in influencing investors’ intention toward Mutual funds. When making decisions about their buying behaviour in the mutual fund industry, retail investors consider data security and additional charges to be key factors. The researcher performed reliability and validity tests, as well as assessed the structural model. The coefficients of determination R2 and Q2 supported the study model and provided evidence of a significant statistical relationship between the independent and dependent variables. Theoretical contribution/Originality: The present study is important as we see more mutual fund folios are getting piled up every year. Also, with the advent of technology, more account holders are getting into digital space. Understanding the awareness and benefits of using digital platforms among retail investors’ decision-making is essential to bringing in more retail participation in the mutual fund industry. Practitioner/Policy implications: These findings can help investors to make investing decisions and are also helpful for regulators or fund managers to attract more investors. Research limitation/Implications: The study can be extended to different regions in India or outside of India to study different perceptions of retail mutual fund investors.